Service Composition for the Semantic Web - Medjahed, Brahim; aBouguettaya, Athman; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Service Composition for the Semantic Web presents an in-depth analysis of aspects related to semantic-enabled Web service modeling and composition. It also covers challenges and solutions to composing Web services on the semantic Web, and proposing a semantic framework for organizing and describing Web services. Service Composition for the Semantic Web describes composability and matching models to check whether semantic Web services can be combined together to avoid unexpected failures at run time, and a set of algorithms that automatically generate detailed descriptions of composite services from high-level specifications of composition requests. The book includes case studies in the areas of digital government and bioinformatics.
Introduction -- Enabling Interactions on the Web: A Taxonomic Perspective -- Describing and Organizing Semantic Web Services -- A Composability Framework for Semantic Web Services -- Context-based Matching for Semantic Web Services -- Towards the Automatic Composition of Semantic Web -- Implementation and Performance -- Conclusion.
Electronic reproduction.
Keywords: Web services; Semantic Web; Electronic book